Institution and Peoples Participation in Watershed Development: Case Study of Teliri Garhwal, Central Himalayas M.L.DuwAN - Dewan, M.L. (Journal of Soil and Water Conservation, 2022)
The Himalayas, the highest and youngest mountain system of the world, on the northern edge of the Indian sub-continent, extend for about 2,400 km from the bend of the Indus river in the west to that of the Brahmaputra in the east. The width of this mountain system is variable-between 400 kms and 160 kills. The total land mass of the Ilimalayan mountain area is 52.3 million hectares out of which the U.P. Himalayas are 4,8 million lb which are the ones where we are doing work in Watershed